Fabrication of glass foams from industrial wastes used as insulating board - K. Pawanawichian (2018)
Insulating glass foam (IGF) was successfully fabricated by wet process. The starting proportion of 65 wt% waste glass, 12 wt% slag, 23 wt% commercial soap was added with 15 wt% Na2SiO3 and represented then was sintered at 725 °C. The IGF had cellular structure with the macro-pore size at 0.428 mm and thin cell walls. Density, thermal conductivity and compressive strength were 0.310 g/cm3, 0.130 W/m.K and 0.78 MPa, respectively. The average pore diameter and porosity increased with increasing the Na2SiO3 concentration and the sintering temperature. On the other hand, the density, thermal conductivity and compressive strength were decreased. © (2013) Trans Tech Publications, Switzerland.